2022
DOI: 10.1021/acs.iecr.2c02489
|View full text |Cite
|
Sign up to set email alerts
|

Catalytic Oxidation of NO over Fe-Doped MnO2 Catalyst

Abstract: Fe-doped MnO 2 (Fe-MnO 2 ) generally exhibits higher NO oxidation activity than MnO 2 , which is widely attributed to the promoting effect of surface chemisorbed oxygen species (O ads ) adsorbed on surface oxygen vacancies (SOVs) generated upon Fe doping. Whether the higher content of SOVs and thus higher content of O ads can be achieved by increasing the content of Fe precursor in synthesis and whether higher content of SOVs in MnO 2 can lead to higher NO oxidation activity remain to be investigated. Herein, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 34 publications
0
6
0
Order By: Relevance
“…It is widely accepted that O ads is associated with the oxygen vacancy in Mn oxides. 21 The O ads /O latt ratio decreases in the following order: OMS-2 S (0.45) > OMS-2 R (0.41) > OMS-2 H (0.39). Figure 4c depicts the Mn 2p spectra of the three catalysts.…”
Section: Resultsmentioning
confidence: 93%
See 3 more Smart Citations
“…It is widely accepted that O ads is associated with the oxygen vacancy in Mn oxides. 21 The O ads /O latt ratio decreases in the following order: OMS-2 S (0.45) > OMS-2 R (0.41) > OMS-2 H (0.39). Figure 4c depicts the Mn 2p spectra of the three catalysts.…”
Section: Resultsmentioning
confidence: 93%
“…The H 2 -TPR profiles of the three catalysts shown in Figure c reveal that OMS-2 S has the lowest reduction temperature, followed by OMS-2 R and then OMS-2 H . This suggests that OMS-2 S has higher oxygen mobility compared to OMS-2 R and OMS-2 H as a lower reduction temperature indicates higher oxygen mobility . This higher oxygen mobility is advantageous for the CO oxidation reaction.…”
Section: Resultsmentioning
confidence: 94%
See 2 more Smart Citations
“…Various catalysts, mainly including metal oxides, molecular sieves, carbon materials, noble metals, and perovskite oxides, have been investigated for NO oxidation . Among these catalysts, non-noble transition metal oxides, represented by MnO 2 , have stood out because of their low cost and relatively good NO oxidation performance. It is reported that the surface-active oxygen species (chemisorbed oxygen especially) in MnO 2 play important roles in catalyzing NO oxidation, and improving the concentration of active oxygen species has been demonstrated to be effective in enhancing catalytic activity. , …”
Section: Introductionmentioning
confidence: 99%